Reduced Platelet Aggregation in Hemolytic-Uremic Syndrome - Kaplan, Bernard S; Fong, Jack S C (Thrombosis and Haemostasis, 1980)
Platelet aggregation was studied in three patients during the course of the hemolytic-uremic syndrome (HUS) when the platelet count was below 100,000/mm3 and after the platelet count had normalized. Platelet aggregation was examined in response to epinephrine, adenosine diphosphate (ADP) and collagen. Aggregation did not occur in response to epinephrine when the patients were thrombocytopenic but normal tracings were obtained when the platelet counts had returned to normal. In contrast, platelet-rich plasma from normal subjects diluted with platelet-poor plasma from patients to comparable platelet counts, showed normal aggregation responses. This study demonstrates that platelet aggregation is reduced in the early phase of the HUS.
Keywords: Platelets aggregation; Hemolytic-uremic syndrome